Global communication models and their importance to public administrations. The case of the Secretariat of Information and Communication Technologies in Cundinamarca - López Villanueva, Cindy Rocío; Martínez Cárdenas, Edgar Enrique; Pico García, Harold David (Cuadernos de Administración, 2018)
This study examines the state of communications in the process of collection of requirements between the Secretariat of Information and Communication Technologies (ICT) of the Government of Cundinamarca and the municipalities of the department, through surveys and interviews with stakeholders and comparative analyses based on the current technical quality standards and variables of the global communication model. The data analyzed suggest that the strategies and instruments of the communication and quality area in the revised process have very little impact, as evidenced by the low levels of knowledge on the technological offer and interaction with stakeholders. Setting off from the global project management model and the systemic analysis approach, recommendations are made to the ICT Secretariat’s requirements collection process, thereby enabling it to strengthen its institutional offer and effectively meeting the needs of the target population.